Visualization analysis of research frontiers and trends in the treatment of sciatic nerve injury - Wang, Yan; Wang, Yahui; Lv, Lijie; Li, Tianyi; Wang, Yan; Pei, Fei (Frontiers in Neurology, 2024)
Objective To visualize and analyze the literature related to sciatic nerve injury treatment from January 2019 to December 2023, and summarize the current status, hotspots, and development trends of research in this field. Methods Using CiteSpace and VOSviewer software, we searched the Web of Science database for literature related to the treatment of sciatic nerve injury. Then we analyzed and plotted visualization maps to show the number of publications, countries, institutions, authors, keywords, references, and journals. Results A total of 2,653 articles were included in the English database. The annual number of publications exceeded 230, and the citation frequency increased yearly. The United States and China were identified as high-influence nations in this field. Nantong University was the leading institution in terms of close cooperation among institutions. The authors Wang Yu had the highest number of publications and were highly influential in this field. Keyword analysis and reference Burst revealed a research focus on nerve regeneration and neuropathic pain, which involve regenerative medicine and neural tissue engineering. Chronic pain resulting from sciatic nerve injury often manifests alongside anxiety, depression, cognitive-behavioral disorders, and other issues. Interventions such as stem cells, electrical stimulation, electroacupuncture, total joint replacement, pharmacological interventions, gene therapy, nerve conduits, chitosan scaffolds, and exercise promote nerve repair and alleviate pain. Schwann cells have been the focus of much attention in nerve repair and regeneration. Improving the outcome of sciatic nerve injury is a current research challenge and focus in this field. Based on keyword Burst, nerve conduits and grafts may become a potential research hotspot in the treatment of sciatic nerve injury. Conclusion This visual analysis summarizes research trends and developments of sciatic nerve injury treatment and predicts potential research frontiers and hot directions.